Persuasive Language in Political Campaign - Fahria Malabar (Jambura Journal of English Teaching and Literature, 2020)
This study is aimed at exploring the persuasive language strategies used by the candidates of mayor of Gorontalo in the mayoral electoral campaign of 2018. The data, in form of utterances, were taken from the speeches of their political campaign by using video recording. After the data were collected, those were firstly classified into the types of persuasive language strategies, then analyzed and interpreted regarding the function and the way the speaker used those strategies to persuade the audience. The result showed that the three candidates used the similar strategies to influence the audience of their political campaign. Those strategies are reason and logic, evidence, attack, appeal to a sense of justice, appeal to the hip-pocket nerve, appeal to patriotism, repetition, and colloquial language. However, based on the interpretation, the different political background of the candidates influenced the way they used the strategies.